Cutaneous basal cell carcinoma with mixed histology: Cytomorphological features of two unusual cases - Goyal, Surbhi (J Cytol, 2017)
Cutaneous basal cell carcinoma (BCC) is a slow growing locally aggressive malignant tumor. It is usually diagnosed on histopathological examination of the excised biopsy. Recently, fine needle aspiration cytology (FNAC) is emerging as a simple alternative technique for rapid diagnostic work of nodular and plaque-like skin lesions. We report the cytomorphological features of two cases of cutaneous BCC having unusual clinical presentation and mixed histology (MH); emphasizing the diagnostic difficulties encountered on cytology, the plausible explanation and the precautions to keep in mind to avoid misdiagnosis.